Evaluation of Laboratory Waste Management at Medan State Polytechnic - Utami, Citra; Septiningtyas, Dina Tri; Fauzi, Indra; Alfiani; Mulyani, Rini; Rita, Eva; Siregar, Gabriella (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The notion of a sustainable campus (green campus) may be used to execute higher education's strategic role in contributing to sustainable development. The Strategic Plan of Medan State Polytechnic, at Strategic Objective Point 7 concerning Improving the Quality of Management of Tridharma Implementation, states that one of Medan State Polytechnic's strategic efforts is to implement sustainable development in the form of a green campus. The scoring evaluation based on categories and waste indicators (WS) based on the UI GreenMetric Guideline World University Rankings 2023 received 75 points out of a possible 1800 points, or 4.3%. Furthermore, efforts are made to improve the waste category's scoring by constructing stabilization ponds comprised of anaerobic ponds, facultative ponds, and maturation ponds for wastewater generated from cleaning laboratory equipment, while the remaining concrete material is used as a mixture of Cement Treated Base (CTB).